The Relationship Between Employee Communication And Performance: An Analysis Of Public Hospitals In Makassar City - Nurdiansyah, Nurdiansyah (Jurnal Ekonomi, 2024)
Health is a global issue that is important to everyone. Based on the performance report of the Indonesian Ministry of Health in the vision (2014-2030), the average health system performance of 47 districts is at 69.72%, while Makassar City only reached 42.69%, placing it at the lowest rank in the entire country. The main causes of the low performance in Makassar City are not yet known with certainty. The literature suggests that organizational performance can be improved through succession planning, job design, workplace recognition, dialogue, and problem solving, among other factors. However, the influence of employee communication on performance has not been studied in depth, especially in Makassar City. This study aims to explore the impact of employee communication on the performance of public health organizations in Makassar City, Indonesia. This study uses Komal and Tahir's System Theory and Employee Participation Model as a reference framework. In a correlational study involving 384 health workers in Makassar City, data were collected through a five-point Likert scale questionnaire that was tested for validity and reliability. The results of the study indicate that employee communication has a positive and significant influence on organizational performance (β=.313, p<.05). Based on these results, it is concluded that the improvement of government health organization performance is influenced by the quality of employee communication. This study recommends that management encourage increased employee involvement in work-related decision making and integrate their views into organizational performance evaluations to increase employee ownership and involvement in the organization. The results of this study can provide benefits for employee voice managers, human resource managers, local governments, and other researchers or academics.